Monte Carlo Calculation of Beam Quality and Phantom Scatter Corrections for Lithium Formate Electron Paramagnetic Resonance Dosimeter for High-energy Brachytherapy Dosimetry - Mishra, Subhalaxmi (J Med Phys, 2017)
PURPOSE: To investigate beam quality correction, K(QQ0) (r) and phantom scatter correction, K(phan) (r) for lithium formate dosimeter as a function of distance r along the transverse axis of the high-energy brachytherapy sources (60)Co, (137)Cs, (192)Ir and (169)Yb using the Monte Carlo-based EGSnrc code system. MATERIALS AND METHODS: The brachytherapy sources investigated in this study are BEBIG High Dose Rate (HDR) (60)Co (model Co0.A86), (137)Cs (model RTR), HDR (192)Ir (model Microselectron) and HDR (169)Yb (model 4140). The solid phantom materials investigated are PMMA, polystyrene, solid water, virtual water, plastic water, RW1, RW3, A150 and WE210. RESULT: K(QQ0) (r) is about unity and distance independent fo (60)Co, (137)Cs and (192)Ir brachytherapy sources, whereas for the (169)Yb source, K(QQ0) (r) increases gradually to about 4 % larger than unity at a distance of 15 cm along the transverse axis of the source. For (60)Co source, phantoms such as polystyrene, plastic water, solid water, virtual water, RW1, RW3 and WE210 are water-equivalent but PMMA and A150 phantoms show distance-dependent K(phan) (r) values. For (137)Cs and (192)Ir sources, phantoms such as solid water, virtual water, RW1, RW3 and WE210 are water-equivalent. However, phantoms such as PMMA, plastic water, polystyrene and A150 showed distance-dependent K(phan) (r) values, for these sources. For (169)Yb source, all the investigated phantoms show distance-dependent K(phan) (r) values. CONCLUSION: K(QQ0) (r) is about unity and distance independent for (60)Co, (137)Cs and (192)Ir brachytherapy sources. Phantoms such as solid water, virtual water, RW1, RW3 and WE210 are water-equivalent for (60)Co, (137)Cs and (192)Ir brachytherapy sources. For (169)Yb source, all the investigated phantoms show distance-dependent K(phan) (r) values.